2021
DOI: 10.1111/ijcp.14753
|View full text |Cite
|
Sign up to set email alerts
|

Thiol levels in mild or moderate COVID‐19 patients: A comparison of variant and classic COVID‐19 cases

Abstract: SARS-CoV-2, also known as Coronavirus-19, is the seventh member of the coronavirus family, which has members such as severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), following its detection in Wuhan in 2019 in a short time, it has turned into a pandemic that has taken the world under its influence. 1 Basically, four variants of concern are mentioned, namely alpha, beta, gamma and delta of the coronavirus family. It is known that the beta type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Most importantly, this study provides convincing evidence of a significant association between serum free thiol concentrations—being a minimally invasive method to quantify systemic oxidative stress—and COVID-19, as these concentrations were evidently reduced in non-hospitalized subjects with relatively mild COVID-19. This cohort of non-hospitalized subjects is unique and provides new evidence on the presence of oxidative stress in COVID-19, complementing previous studies [ 7 , 8 ], but this time specifically for milder cases. The short-term follow-up with clinical and biochemical data available at both day 0 and day 7 allowed us to make observations over time in the disease course.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Most importantly, this study provides convincing evidence of a significant association between serum free thiol concentrations—being a minimally invasive method to quantify systemic oxidative stress—and COVID-19, as these concentrations were evidently reduced in non-hospitalized subjects with relatively mild COVID-19. This cohort of non-hospitalized subjects is unique and provides new evidence on the presence of oxidative stress in COVID-19, complementing previous studies [ 7 , 8 ], but this time specifically for milder cases. The short-term follow-up with clinical and biochemical data available at both day 0 and day 7 allowed us to make observations over time in the disease course.…”
Section: Discussionsupporting
confidence: 68%
“…Taken together, a systemic disbalance in redox status is considered to be part of the complex pathogenesis of COVID-19, providing a therapeutic target that could especially benefit individuals with an already impaired redox balance [ 5 , 6 ]. Although strong on theoretical grounds with upcoming studies providing direct evidence of oxidative stress in COVID-19, the exact role of oxidative stress in COVID-19 remains unclear and biomarkers to evaluate the redox status in COVID-19 are urgently needed [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In COVID-19 patients, serum levels of glutathione and total thiol are decreased, while levels of superoxide dismutase, catalase, malondialdehyde (a marker of oxidative stress and lipoperoxidation) and the total oxidant status are increased [ 57 , [80] , [81] , [82] ]. Oxidative stress levels correlated with blood oxygen saturation levels, disease severity, prognosis, and with the virus variant that was causing the infection [ 57 , 80 , 82 , 83 ]. Mechanistically, an analysis of transcriptome changes observed in different data sets from blood cells, lung biopsies or leukocytes from healthy subjects and COVID-19 patients showed that there is a significant upregulation of pro-oxidant genes, principally the myeloperoxidase and calprotectin genes [ 84 ].…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
“… 47 , 48 In this regard, it was found that thiol levels are low in COVID‐19 patients. 49 The role of oxidative stress in COVID‐19 pathology is further supported by potential positive impact of oral and intravenous glutathione (GSH) and N‐acetylcysteine (NAC) on the cytokine storm and ARDS in COVID‐19 patients. 50 , 51 Likewise, ascorbic acid (vitamin C) and curcumin exert various pharmacological effects including anti‐bacterial, anti‐cancer, anti‐inflammatory, immuno‐modulatory, anti‐oxidant, anti‐fungal, anti‐mutagenic, and anti‐viral activities, 52 which may have contributed to the obtained beneficial effects of ArtemiC.…”
Section: Discussionmentioning
confidence: 99%